A single-phase AB3 superlattice hydrogen storage alloy and preparation method thereof

Through methods such as separate smelting and belt smelting, single-phase AB3 superlattice hydrogen storage alloy was prepared, which solved the problem of insufficient hydrogen storage density and cycle stability in the existing technology, and achieved high hydrogen storage density and long life. Effect.

CN119120990BActive Publication Date: 2025-02-25GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411605686.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The prior art is difficult to prepare single-phase AB3 type superlattice hydrogen storage alloys, resulting in insufficient hydrogen storage density and cycle stability.

Method used

By smelting the Mg element raw materials separately from other metal elemental raw materials, and using belt smelting and heat treatment methods, the Mg element content and alloy phase structure are accurately controlled to form a single-phase AB3 type superlattice crystal phase structure.

Benefits of technology

A hydrogen storage alloy with high hydrogen storage density and long life has been achieved, with hydrogen absorption reaching more than 1.8 wt%, effective hydrogen release reaching more than 1.7 wt%, and the capacity retention rate of 200 cycles reaches more than 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of hydrogen storage alloys, and specifically discloses a single-phase AB3 superlattice hydrogen storage alloy and a preparation method thereof. The hydrogen storage alloy of the present invention has a single-phase AB3 type crystal phase structure, which is different from other multi-phase or single-phase A2B7, A5B 19 The hydrogen storage alloy has higher hydrogen storage capacity and cycle stability. The hydrogen absorption amount reaches more than 1.8wt.%, the effective hydrogen release amount reaches more than 1.7wt.%, and the capacity retention rate after 200 cycles reaches more than 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogen storage alloys, and specifically relates to a single-phase AB 3 Type superlattice hydrogen storage alloy and preparation method thereof. Background Art

[0002] According to domestic and foreign research reports, rare earth hydrogen storage materials are m B n The naming is in the form of, where A is an element with strong affinity for hydrogen and can react with hydrogen to produce hydrides, mainly rare earth elements, Ti, Mg, Zr, V, etc.; B is a control element for hydrogen transmission and release, mainly transition metals such as Ni, Co, Cr, etc.; element B generally does not react with hydrogen, but after forming an alloy with A, it can catalyze the absorption and release of hydrogen. Common rare earth hydrogen storage materials include AB 5 Type, superlattice type (such as AB 3 , A 2 B 3 , A 5 B 19 , AB 4 etc.) and rare earth modified materials, etc.

[0003] AB 5 Type hydrogen storage alloy materials (such as LaNi 5 ) has the advantages of easy activation and good cycle stability, but its weight hydrogen storage density is relatively low (about 1.4wt%), which restricts its application in gas-solid hydrogen storage (hydrogen energy and fuel cells, etc.). In order to improve the weight hydrogen storage density, new rare earth hydrogen storage materials with superlattice structures have become a research hotspot in recent years. The crystal structure of rare earth superlattice hydrogen storage materials is composed of [A 2 B 4 ] and [AB 5 ] subunits are stacked along the c-axis, so this type of hydrogen storage material has both AB 2 Type alloy high capacity characteristics and AB 5 The National Research Institute in Osaka, Japan, has developed high-performance PuNi using powder metallurgy technology and light element substitution. 3 Type superlattice hydrogen storage material (AB 3 Type), the reversible hydrogen storage and desorption density at room temperature reaches more than 1.8wt%, which is significantly higher than that of traditional AB 5 Type hydrogen storage materials. Many researchers in my country have also conducted research on superlattice hydrogen storage materials for gas-solid hydrogen storage. The room temperature hydrogen storage density of the obtained materials exceeds 1.7wt%, but the room temperature hydrogen release density is only 1.4~1.6wt%. In addition to hydrogen storage capacity, the cycle life of rare earth hydrogen storage materials is also crucial. Ibaraki University in Japan discovered that Mg replaces Pr to form Pr1-xMgxNi 3Alloys can anisotropically shrink the unit cell volume to reversibly adsorb and desorb hydrogen and prevent the alloy structure from changing. 2 B 4 ] and [AB 5 ]Asynchronous expansion and contraction between sublattices will cause stress in the super-stacking structure of the alloy, thereby destroying the cycle stability. Shanghai University found that a small amount of Mg replacing Y can significantly inhibit the hydrogen-induced amorphization of the La-Y-Ni system, while improving the electrochemical capacity and the cycle capacity retention rate by 1 times. Therefore, by adding Mg, the regulation of superlattice subunits and the replacement of lightweight elements, as well as the matching adjustment between unit cell size and subunits can be achieved, which is expected to develop new rare earth hydrogen storage materials with high hydrogen storage density and long life.

[0004] However, due to the light weight and low melting point of Mg, in the preparation process of hydrogen storage alloys, the melting temperature or heat treatment temperature generally exceeds the melting point of Mg, which is easy to float, volatilize, and adhere to the equipment, resulting in uneven distribution of Mg in the hydrogen storage alloy, and uncontrollable Mg content. In addition, there are generally multiple types of alloy phase structures in the prepared hydrogen storage alloy, which reduces the weight hydrogen storage density and life of the hydrogen storage alloy. Therefore, at present, the process of using Mg to regulate the crystal phase structure and state of hydrogen storage alloys is still immature, and it is impossible to efficiently obtain a single-phase hydrogen storage alloy through a simple process to achieve the purpose of improving the weight hydrogen storage density and life of the hydrogen storage alloy. Summary of the invention

[0005] In view of the problem that the above-mentioned prior art involves the process of using Mg to regulate the crystal phase structure and state of hydrogen storage alloys, it is difficult to obtain a single-phase hydrogen storage alloy. 3 Type superlattice hydrogen storage alloy and preparation method thereof.

[0006] To achieve the above purpose, the following technical solutions are specifically included:

[0007] A hydrogen storage alloy having a general chemical formula of Y 1-x-y A x Mg y Ni 3-z B z , wherein x, y, and z are stoichiometric ratios, and the values ​​of x, y, and z satisfy the following formula: 0≤x≤0.2, 0.1<y≤0.2, 0≤z≤0.2, A includes at least one element of Sm, La, and Ca, and B includes at least one element of Co, Cr, Zn, and Mo; the hydrogen storage alloy is a single-phase AB 3 Type crystal phase structure.

[0008] The hydrogen storage alloy of the present invention is a single-phase AB 3 Type superlattice crystal phase structure, which is different from other multiphase or single phase A 2B 7 , A 5 B 19 Hydrogen storage alloys have higher hydrogen storage capacity and cycle stability.

[0009] Preferably, the hydrogen storage alloy comprises at least one of the following chemical formulas: 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , Y 0.85 Mg 0.15 Ni 3 , Y 0.8 La 0.05 Mg 0.15 Ni 3 .

[0010] Preferably, the hydrogen storage alloy has (Y, Mg) 1 Ni 3 Crystal phase.

[0011] A method for preparing the hydrogen storage alloy comprises the following steps:

[0012] (1) According to the chemical formula Y 1-x-y A x Mg y Ni 3-z B z The stoichiometric ratio and the use of the simple substances of each element as raw materials for batching;

[0013] (2) smelting the single element raw materials of each element except the single element raw material of Mg;

[0014] (3) adding Mg single substance raw material for smelting to obtain alloy melt;

[0015] (4) performing belt-spinning smelting on the alloy melt to obtain an alloy belt;

[0016] (5) The alloy is subjected to heat treatment to obtain the hydrogen storage alloy.

[0017] In the method of the present invention, the Mg single substance raw material and other metal element single substance raw materials are first smelted separately, and then the alloy melt is formed by a belt spinning method, and finally the alloy belt is heat treated. The various processes cooperate with each other, and the Mg element content can be accurately controlled, the alloy phase structure is optimized, and the purpose of improving the alloy performance is achieved.

[0018] The method of the present invention can overcome the defects of uneven distribution of Mg element, difficult control of Mg element content and the existence of multiple types of crystal phases in the alloy, and obtain a single-phase AB 3This type of hydrogen storage alloy has high hydrogen storage density and long hydrogen storage life.

[0019] Preferably, in step (1), when the ingredients are prepared, the chemical formula Y 1-x-y A x Mg y Ni 3-z B z Calculated based on the mass of Mg element in the raw material, the content of Mg element is in excess of 15-30wt.%.

[0020] The present invention increases the Mg content in the alloy by adding an excessive amount of Mg, further accurately controls the Mg content, improves lattice stability, and further improves the hydrogen storage performance of the hydrogen storage alloy.

[0021] Preferably, in step (2), the smelting is performed by induction smelting, the power of the induction smelting is 15-20 kW, and the time of the induction smelting is 20-30 min.

[0022] Preferably, in step (3), the smelting is performed by induction smelting, the power of the induction smelting is 10-15 kW, and the time of the induction smelting is 4-8 min.

[0023] Preferably, in step (4), the belt smelting rate is 0.5-1.5 m / s.

[0024] Preferably, in step (5), the heat treatment temperature is 900-950°C, the heat treatment time is 2-6h, and the heating rate when heating to the heat treatment temperature is 5-10°C / min.

[0025] Compared with the prior art, the present invention has the following beneficial effects: the hydrogen storage alloy of the present invention is a single-phase AB 3 The superlattice crystal phase structure has a high hydrogen storage density and a long hydrogen storage life. The hydrogen absorption capacity reaches more than 1.8wt.%, the effective hydrogen release capacity reaches more than 1.7wt.%, and the capacity retention rate after 200 cycles reaches more than 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of the hydrogen storage alloy of Example 1.

[0027] Figure 2 This is the SEM image of the hydrogen storage alloy of Comparative Example 1.

[0028] Figure 3 This is the SEM image of the hydrogen storage alloy of Comparative Example 3.

[0029] Figure 4 This is the SEM image of the hydrogen storage alloy of Comparative Example 4. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0031] Example 1

[0032] A method for preparing a hydrogen storage alloy comprises the following steps:

[0033] (1) In terms of molar ratio, according to the chemical formula Y 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , take the single substance of each metal element as raw material, and make ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0034] (2) In a 5 kg-class belt-swinging induction melting furnace, the single element raw materials of Y, Sm, Ni, and Co, except for the single element raw material of Mg, are melted at a melting power of 18 kW and a melting time of 20 min;

[0035] (3) Add Mg single substance raw material for smelting at a smelting power of 12 kW and a smelting time of 5 min to obtain a uniform alloy melt;

[0036] (4) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 1.5 m / s to obtain the alloy belt-spinning;

[0037] (5) The alloy is spun on a belt, and the temperature is increased from room temperature to 950° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 5 h. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0038] Example 2

[0039] A method for preparing a hydrogen storage alloy comprises the following steps:

[0040] (1) In terms of molar ratio, according to the chemical formula Y 0.85 Mg 0.15 Ni 3, take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0041] (2) In a 5 kg-class belt induction melting furnace, the Y and Ni elemental raw materials except the Mg elemental raw material are melted at a melting power of 20 kW and a melting time of 30 min;

[0042] (3) Add Mg single-element raw material for smelting at a smelting power of 15 kW and a smelting time of 5 min to obtain a uniform alloy melt;

[0043] (4) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 0.8 m / s to obtain the alloy belt-spinning;

[0044] (5) The alloy is spun on a belt, and the temperature is increased from room temperature to 950° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 4 h. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0045] Example 3

[0046] A method for preparing a hydrogen storage alloy comprises the following steps:

[0047] (1) In terms of molar ratio, according to the chemical formula Y 0.8 La 0.05 Mg 0.15 Ni 3 , take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0048] (2) In a 5 kg-class belt-swinging induction melting furnace, the Y, La, and Ni elemental raw materials except the Mg elemental raw material are melted at a melting power of 20 kW and a melting time of 20 min;

[0049] (3) Add Mg single-element raw material for smelting at a smelting power of 15 kW and a smelting time of 3 min to obtain a uniform alloy melt;

[0050] (4) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 1.5 m / s to obtain the alloy belt-spinning;

[0051] (5) The alloy is spun on a belt, and the temperature is increased from room temperature to 925° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 3 h. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0052] Example 4

[0053] A method for preparing a hydrogen storage alloy comprises the following steps:

[0054] (1) In terms of molar ratio, according to the chemical formula Y 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0055] (2) In a 5 kg-class belt-swinging induction melting furnace, the single element raw materials of Y, Sm, Ni, and Co, except the single element raw material of Mg, are melted at a melting power of 19 kW and a melting time of 25 min;

[0056] (3) Mg single substance raw material is added for smelting at a smelting power of 12 kW and a smelting time of 4 min to obtain a uniform alloy melt;

[0057] (4) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 1 m / s to obtain the alloy belt-spinning;

[0058] (5) The alloy is spun on a belt, and the temperature is increased from room temperature to 950° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 6 hours. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that this comparative example does not adopt the belt-swinging method to form, but adopts the casting ingot method to form, and includes the following steps:

[0061] (1) In terms of molar ratio, according to the chemical formula Y 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co0.1 , take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0062] (2) In a 5 kg-class belt-swinging induction melting furnace, the single element raw materials of Y, Sm, Ni, and Co, except for the single element raw material of Mg, are melted at a melting power of 18 kW and a melting time of 20 min;

[0063] (3) Add Mg single substance raw material for smelting at a smelting power of 12 kW and a smelting time of 5 min to obtain a uniform alloy melt;

[0064] (4) casting the alloy melt, and naturally cooling it after casting to obtain an ingot;

[0065] (5) The ingot is heated from room temperature to 950° C. at a heating rate of 5° C. / min, kept at this temperature for 5 h, and then cooled to room temperature in the furnace to obtain a hydrogen storage alloy.

[0066] Comparative Example 2

[0067] The difference between this comparative example and Example 1 is that this comparative example does not perform heat treatment on the alloy strip, and includes the following steps:

[0068] (1) In terms of molar ratio, according to the chemical formula Y 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0069] (2) In a 5 kg-class belt-swinging induction melting furnace, the single element raw materials of Y, Sm, Ni, and Co, except for the single element raw material of Mg, are melted at a melting power of 18 kW and a melting time of 20 min;

[0070] (3) Add Mg single substance raw material for smelting at a smelting power of 12 kW and a smelting time of 5 min to obtain a uniform alloy melt;

[0071] (4) The alloy melt is subjected to belt melting at a belt melting speed of 1.5 m / s to obtain the hydrogen storage alloy.

[0072] Comparative Example 3

[0073] The difference between this comparative example and Example 1 is that this comparative example does not feed the Mg element single substance raw material and other element single substance raw materials separately, and includes the following steps:

[0074] (1) In terms of molar ratio, according to the chemical formula Y 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0075] (2) In a 5 kg-class belt induction melting furnace, the single element raw materials of Mg, Y, Sm, Ni and Co are melted at a melting power of 18 kW and a melting time of 20 min to obtain an alloy melt;

[0076] (3) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 1.5 m / s to obtain the alloy belt-spinning;

[0077] (4) The alloy is spun on a belt, and the temperature is increased from room temperature to 950° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 5 h. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the alloy composition of this comparative example is Y 0.8 La 0.05 Mg 0.15 Ni 2 , including the following steps:

[0080] (1) In terms of molar ratio, according to the chemical formula Y 0.8 La 0.05 Mg 0.15 Ni 2, take the single substance of each element as raw material, and prepare the ingredients, wherein the total mass of the single substance raw materials of each element is 3kg, based on the mass of the Mg element converted in the above chemical formula, an excess of 20wt.% is added, that is, the mass of the Mg element converted in the above chemical formula is m 1 The mass of the Mg elemental raw material is expressed as m, then m=m 1 +m 1 *20%;

[0081] (2) In a 5 kg-class belt-swinging induction melting furnace, the Y, La, and Ni elemental raw materials except the Mg elemental raw material are melted at a melting power of 18 kW and a melting time of 20 min;

[0082] (3) Add Mg single substance raw material for smelting at a smelting power of 12 kW and a smelting time of 5 min to obtain a uniform alloy melt;

[0083] (4) subjecting the alloy melt to belt-spinning smelting at a belt-spinning speed of 1.5 m / s to obtain the alloy belt-spinning;

[0084] (5) The alloy is spun on a belt, and the temperature is increased from room temperature to 950° C. at a heating rate of 5° C. / min, and the temperature is kept at this temperature for 5 h. The alloy is then cooled to room temperature in a furnace to obtain the hydrogen storage alloy.

[0085] The alloys prepared in the above-mentioned embodiments and comparative examples were subjected to performance tests, and the specific test methods are as follows:

[0086] (1) Phase structure and phase content (wt.%): XRD was used to characterize the phase of the alloy sample, and GSAS was used to refine the XRD data to obtain the lattice constant;

[0087] (2) Hydrogen absorption and effective hydrogen desorption (wt.%): After the alloy sample is activated, the PCT curve test is carried out at 25°C and 8MPa hydrogen pressure to obtain the hydrogen absorption and effective hydrogen desorption above 0.1MPa;

[0088] (3) 200-cycle capacity retention rate (%): Hydrogen absorption for 30 min at 25 °C and 8 MPa hydrogen pressure, followed by vacuuming at 25 °C for 30 min, as one cycle to test the hydrogen absorption capacity retention rate of the alloy;

[0089] (3) Alloy micromorphology: scanning electron microscopy (SEM).

[0090] The test results are shown in Table 1 and Appendix Figure 1-4 shown.

[0091] Table 1

[0092]

[0093] The above embodiments are combined with the attached Figure 1 As shown in Table 1, the hydrogen storage alloys of the present invention are all single-phase AB 3 Type, i.e. (Y,Mg) 1 Ni 3 Crystalline phase, the hydrogen absorption capacity reaches more than 1.8wt.%, the effective hydrogen release capacity reaches more than 1.7wt.%, and the capacity retention rate after 200 cycles reaches more than 95%. It has high hydrogen storage density and long cycle life.

[0094] In the embodiment and comparative example 1, Figure 2 As shown in Table 1, after the hydrogen storage alloy in Comparative Example 1 is conventionally cast and cooled, Mg has a lower melting point and is significantly different from other components, so it is unevenly distributed in the alloy, resulting in AB in the alloy. 5 phase, resulting in a decrease in the amount of hydrogen absorbed and desorbed by the alloy. The presence of multiple phases in the alloy causes serious pulverization of the alloy during hydrogen absorption and desorption, the superlattice structure is prone to collapse, and the cycle performance is reduced.

[0095] In Example 1 and Comparative Example 2, combined with Table 1, it can be seen that heat treatment of the alloy strip can stabilize the phase structure of the alloy, improve the uniformity of the alloy, and reduce the lattice stress of the alloy; the alloy strip in Comparative Example 2 was not heat treated, resulting in a multiphase structure of the alloy, and the platform slope factor in the PCT curve was large, indicating that the amount of hydrogen absorption and desorption was reduced.

[0096] In Example 1 and Comparative Example 3, Figure 3 As can be seen from Table 1, the Mg raw material in Comparative Example 3 is directly fed together with other elements, resulting in severe Mg volatilization, insufficient Mg content in the alloy, poor repeatability, difficulty in forming a superlattice structure, and reduced hydrogen storage capacity.

[0097] In Example 1 and Comparative Example 4, Figure 4 As shown in Table 1, the alloy in Comparative Example 4 forms a multiphase structure, and the hydrogen storage and release capacity is reduced. Therefore, different alloy components will significantly affect the crystal phase composition of the alloy.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A hydrogen storage alloy, characterized in that Its chemical formula is Y 1-x-y A x Mg y Ni 3-z B z , wherein x, y, z are stoichiometric ratios, and the values ​​of x, y, z satisfy the following formulas: 0≤x≤0.2, 0.1<y≤0.2, 0≤z≤0.2, A is at least one element selected from Sm, La, and Ca, and B is at least one element selected from Co, Cr, Zn, and Mo; the hydrogen storage alloy is a single-phase AB3 type crystal structure; the hydrogen storage alloy has a (Y, Mg)1Ni3 crystal phase; the hydrogen absorption capacity of the hydrogen storage alloy reaches more than 1.8wt.%, and the effective hydrogen release capacity of the hydrogen storage alloy reaches more than 1.7wt.%.

2. The hydrogen storage alloy according to claim 1, characterized in that The hydrogen storage alloy comprises at least one of the following chemical formulas: 0.7 Sm 0.15 Mg 0.15 Ni 2.9 Co 0.1 , Y 0.85 Mg 0.15 Ni3, Y 0.8 La 0.05 Mg 0.15 Ni3.

3. A method for preparing the hydrogen storage alloy according to claim 1 or 2, characterized in that: The steps include: (1) According to the chemical formula Y 1-x-y A x Mg y Ni 3-z B z The stoichiometric ratio and the use of the simple substances of each element as raw materials for batching; (2) smelting the single element raw materials of each element except the single element raw material of Mg; (3) adding Mg single substance raw material for smelting to obtain alloy melt; (4) performing belt-spinning smelting on the alloy melt to obtain an alloy belt; (5) The alloy is subjected to heat treatment to obtain the hydrogen storage alloy.

4. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In step (1), when the ingredients are prepared, the chemical formula Y 1-x-y A x Mg y Ni 3-z B z Calculated based on the mass of Mg element in the raw material, the content of Mg element is in excess of 15-30wt.%.

5. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In step (2), the smelting is performed by induction smelting, the power of the induction smelting is 15-20 kW, and the time of the induction smelting is 20-30 min.

6. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In step (3), the smelting is performed by induction smelting, the power of the induction smelting is 10-15 kW, and the time of the induction smelting is 4-8 min.

7. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In step (4), the belt smelting rate is 0.5-1.5 m / s.

8. The method for preparing a hydrogen storage alloy according to claim 3, characterized in that: In step (5), the heat treatment temperature is 900-950°C, the heat treatment time is 2-6h, and the heating rate when heating to the heat treatment temperature is 5-10°C / min.

Citation Information

Patent Citations

  • Hydrogen-storage alloy for low-pressure solid-state hydrogen storage and preparation method thereof

    CN112877567A